Niobium pentachloride promoted synthesis of tetrahydropiridines by multicomponent reaction - Martins, Lucas Lichelão; Silva, Bruno Sacoman Torquato da; Menezes, Manoel Lima de [UNESP]; Silva Filho, Luis Carlos da [UNESP] (My University, 2013)
One-pot multicomponent synthesis of tetrahydropyridine derivatives between aniline derivatives, benzaldehyde and two different β-keto ester (methyl and ethyl acetoacetate) using niobium pentachloride as catalyst under mild conditions, providing good yields.
Keywords: Tetrahydropiridines derivatives; Niobium Pentachloride; Multicomponent reaction; Natural products